Factors analysis of unwanted pregnancies among women childbearing age in Indonesia: analysis of demographic and health survey data in 2017 - Supriyadi, Supriyadi; Yanti, Linda (MEDISAINS, 2020)
Background: Unwanted pregnancies were one of the serious threats to human development around the world. This analysis identifies factors associated with unwanted pregnancies, including intrapersonal, interpersonal, and institutional health services.Objective: We analyzed the extent of unwanted pregnancies and how they predict factors related to Indonesia's unwanted pregnancies.Methods: We analyzed data from the Indonesian Demographic and Health Survey (IDHS) in 2017. Descriptive statistics on the prevalence of unwanted pregnancies and correlated factors. Multiple logistic regression was used to examine the association between intrapersonal factors, interpersonal factors, and community factors with unwanted pregnancies.Results: Participants reported that their most recent was 83.8% indicated a desired pregnancy and 16.2% were unwanted. Multivariate analysis shows the age of the woman (OR=1.37), economic status (OR=1.05), number of children (OR=1.47), contraception failure (OR=0.78), and health worker intervention (OR=1.27) was found to significantly increase the risk of unwanted pregnancy (p<0.05). The number of children is the most substantial factor in unwanted pregnancy among women childbearing in Indonesia.Conclusions: Nearly a fifth of pregnancies among vulnerable women in Indonesia are unwanted pregnancies. WomenEnglish translation.  should plan pregnancy according to the target number of children desired with a partner.